Solid waste management in building construction site - Juliana, Junaidi (2016)
The construction industry is one of the key economic development activities in Malaysia. An increase in the construction sector also contributed to the increase in environmental pollution. Among the causes of environmental problems is the removal and disposal of construction waste is not controlled. Construction waste from construction work, renovation work, the work of demolishing illegally constructed buildings of all types of buildings, whether residential buildings or buildings not dwellings. Construction waste management a very important systematic practiced at the construction site. Alternative measures such as, the cycle must be performed because wastage is not only detrimental to both the contractor and the client but also cause loss of natural resources and the country's economic resources. This research related to the construction of solid waste at the construction site of the building that is to identify the factors and the amount of waste at the construction site and the construction of solid waste that can be recycled. The scope of the study includes the Solid construction waste in building construction site in area of Kuala Lumpur. The objective for this project was achieved through literature review, questionnaires, observations on a construction site, and interviews were done against the contractor. The data obtained showed comparison between Semi D housing projects and building High Rise. This research has found that for housing projects have the highest rate of Semi D for the composition of waste building materials by 17% for the rest of the building materials wood/plywood. The composition of the second highest for debris from construction projects this is Semi D concrete/Mortar and Tiles by 13%. For High Rise building project, the concrete/mortar and wood/plywood is the highest composition of residues from waste which overall 15% respectively. The composition of the second highest for the rest of this material was stone aggregate, sand and steel/iron reinforcement by 13%. This study also covers the frequency of this building material waste reused and causes of the occurrence of wastage at construction sites.